2018
DOI: 10.3390/ijms19123742
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs as Mediators of Tumor Microenvironment and Liver Cancer Cell Communication

Abstract: The tumor microenvironment is an important concept that defines cancer development not only through tumor cells themselves but also the surrounding cellular and non-cellular components, including stromal cells, blood vessels, infiltrating inflammatory cells, cancer stem cells (CSC), cytokines, and growth factors, which act in concert to promote tumor cell survival and metastasis. Hepatocellular carcinoma (HCC) is one of the most common and aggressive human malignancies worldwide. Poor prognosis is largely attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 124 publications
0
30
0
Order By: Relevance
“…Accumulating evidence suggests that lncRNAs play important roles in the regulation of immune-related processes [44,45]. In addition, it is widely recognized that lncRNAs are important regulatory factors in modulating the TIME and tumor progression [30,46]. Therefore, we constructed a functional lncRNA-mRNA co-expressed network using genes exhibiting expression differences between the high and low IS HNSCC male subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that lncRNAs play important roles in the regulation of immune-related processes [44,45]. In addition, it is widely recognized that lncRNAs are important regulatory factors in modulating the TIME and tumor progression [30,46]. Therefore, we constructed a functional lncRNA-mRNA co-expressed network using genes exhibiting expression differences between the high and low IS HNSCC male subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…To date, evidence has shown that some lncRNAs (e.g., TSLNC8, MEG3) function as tumor suppressors [26,27], whereas others (e.g., HOTAIR, PVT1) serve as onco-lncRNAs [28,29]. Recent reports also state that lncRNAs can function by mediating the TME [30,31]; however, their potential regulatory roles in the TME and HNSCC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive and in-depth research on the TME should importantly involve noncoding RNAs (ncRNAs), such as microRNAs (miRNAs) [10][11][12] and long ncRNAs (lncRNAs) [13][14][15]. With the broad application of highthroughput RNA sequencing (RNA-seq), numerous circular RNAs (circRNAs) have been identified and characterized in humans and other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional transcriptome studies focus on protein-coding genes. However, more than 90% of the mammalian genome has been reported to be composed of ncRNAs [9]. Typically, ncRNAs can be divided into housekeeper and regulatory ncRNAs.…”
Section: Introductionmentioning
confidence: 99%